A winged-helix DNA-binding protein is essential for self-fertility during sexual development of the homothallic fungus Fusarium graminearum - Jiyeun Park; Hosung Jeon; Aram Hwangbo; Kyunghun Min; Jaeho Ko; Jung-Eun Kim; Sieun Kim; Ji Young Shin; Yong-Hwan Lee; Yin-Won Lee; Hokyoung Son (mSphere, 2024)
ABSTRACT Sexual reproduction is crucial for increasing the genetic diversity of populations and providing overwintering structures, such as perithecia and associated tissue, in the destructive plant pathogenic fungus Fusarium graminearum. While mating-type genes serve as master regulators in fungal sexual reproduction, the molecular mechanisms underlying this process remain elusive. Winged-helix DNA-binding proteins are key regulators of embryogenesis and cell differentiation in higher eukaryotes. These proteins are implicated in the morphogenesis and development of several fungal species. However, their involvement in sexual reproduction remains largely unexplored in F. graminearum. Here, we investigated the function of winged-helix DNA-binding proteins in vegetative growth, conidiation, and sexual reproduction, with a specific focus on the FgWING27, which is highly conserved among Fusarium species. Deletion of FgWING27 resulted in an abnormal pattern characterized by a gradual increase in the expression of mating-type genes during sexual development, indicating its crucial role in the stage-specific genetic regulation of MAT genes in the late stages of sexual development. Furthermore, using chromatin immunoprecipitation followed by sequencing analysis, we identified Fg17056 as a downstream gene of Fgwing27, which is essential for sexual reproduction. These findings underscore the significance of winged-helix DNA-binding proteins in fungal development and reproduction in F. graminearum, and highlight the pivotal role of Fgwing27 as a core genetic factor in the intricate genetic regulatory network governing sexual reproduction.IMPORTANCEFusarium graminearum is a devastating plant pathogenic fungus causing significant economic losses due to reduced crop yields. In Fusarium Head Blight epidemics, spores produced through sexual and asexual reproduction serve as inoculum, making it essential to understand the fungal reproduction process. Here, we focus on winged-helix DNA-binding proteins, which have been reported to play crucial roles in cell cycle regulation and differentiation, and address their requirement in the sexual reproduction of F. graminearum. Furthermore, we identified a highly conserved protein in Fusarium as a key factor in self-fertility, along with the discovery of its direct downstream genes. This provides crucial information for constructing the complex genetic regulatory network of sexual reproduction and significantly contribute to further research on sexual reproduction in Fusarium species.